Maintenance Scheduling for Buildings Using Fuzzy Logic Application - I Nyoman Dita Pahang Putra; I Gede Susrama Mas Diyasa; Anak Agung Diah Parami Dewi; Bambang Trigunarsyah (Institute for Research and Community Services, Udayana University, 2025)
This research proposes an innovative approach to building maintenance scheduling using fuzzy logic. Fuzzy logic addresses uncertainty and complexity in decision-making processes concerning prioritizing and scheduling maintenance tasks. This study aims to enhance the efficiency of maintenance scheduling, reduce maintenance costs, and consider the variability in building conditions. Traditional methods, such as PERT (Program Evaluation and Review Technique) and CPM (Critical Path Method), have limitations in accurately predicting scheduling times. At the same time, fuzzy logic offers a more precise approach to overcoming uncertainty. Implementing a maintenance scheduling model based on fuzzy logic is expected to yield a more adaptive and responsive maintenance plan in response to changes in building conditions. The results of this research are expected to contribute positively to building maintenance management by leveraging the advantages of fuzzy logic in addressing the challenges of complexity and uncertainty in building maintenance management. By applying fuzzy logic-based maintenance scheduling, it is hoped that precise and efficient building maintenance scheduling can be achieved, thereby minimizing project completion time and assisting project managers. The fuzzy logic method can be employed for construction project scheduling according to the schedule determined by the contractor. This allows the contractor to use it as a consideration for the total duration, along with detailed timing in the project proposal. For the owner, it provides insights into the potential project completion time.